2021
DOI: 10.25115/eea.v39i10.6300
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors on Destination Food Image among International Tourists in Malaysia

Abstract: This study aimed to identify factors influencing destination food image among the international tourists in Malaysia. Food tourism is becoming a trend among tourists. By trying different foods from different countries, tourists able to understand and gained knowledge on the country’s culture. In Malaysia, the food knowledge among the international tourists are limited. Although there are several Malaysian foods which are popular, it still remained unknown for the tourists. This caused international tourists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The study aims to highlight the importance of regional cuisine to visitors as well as the creation and promotion of destination tourism products in the Indian state of Odisha. To assess the relationship between the dimensionsattitude, social media, local food experience, culture & advertisement and destination food image, Osman et al, (2021) carried out research amongst international tourists in Malaysia and found all the dimensions had a positive and significant relationship except social media. Keeping in view the empirical research on factors influencing food destination image (Osman et al, 2021) is scarce and in spite of this fact, the impact of food image on traveller's destination has not been systematically investigated with limited attention given to the development of a measurement scale based on to urists' perception (Hashemi et al, 2023), In order to assess the potential and viability of food tourism in the state of Odisha, India, the current study intends to investigate the elements influencing destination food image (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The study aims to highlight the importance of regional cuisine to visitors as well as the creation and promotion of destination tourism products in the Indian state of Odisha. To assess the relationship between the dimensionsattitude, social media, local food experience, culture & advertisement and destination food image, Osman et al, (2021) carried out research amongst international tourists in Malaysia and found all the dimensions had a positive and significant relationship except social media. Keeping in view the empirical research on factors influencing food destination image (Osman et al, 2021) is scarce and in spite of this fact, the impact of food image on traveller's destination has not been systematically investigated with limited attention given to the development of a measurement scale based on to urists' perception (Hashemi et al, 2023), In order to assess the potential and viability of food tourism in the state of Odisha, India, the current study intends to investigate the elements influencing destination food image (Figure 1).…”
Section: Introductionmentioning
confidence: 99%